Deformation behavior and its mechanism of Al–Zn–Mg–Cu alloys in different heat treatment states under electrically-assisted uniaxial tension - Yanli Song; Long Chen; Chuanchuan Hao; Hainan Xu; Lin Hua; Jue Lu; Lechun Xie; Qian Sun (Journal of Materials Research and Technology)
Electrically-assisted manufacturing has proven to be an efficient process in improving formability for metal alloys. However, there are relatively few studies on the mechanism of the deformation behavior of Al–Zn–Mg–Cu alloys in different heat-treated states under electrically-assisted quasi-static uniaxial tension (EAT). This study presents the effects of EAT on the mechanical properties and microstructure of materials. The results showed that under suitable EAT parameters, the true strain of AA 7075-T6 is reduced by about 12.04 %, while the true strain of AA 7075-O is significantly increased by about 78.79 %. The electrical current reduces dislocation density, refines the recrystallized grains and increases the Cube texture content in AA 7075-O. From thermodynamic and kinetic perspectives, the athermal effects induced by electrical current are beneficial in promoting the dynamic dissolution of the metastable phase in AA 7075-T6 and the local dynamic precipitation of the GPII region in AA 7075-O, respectively. The stress drops and strain hardening behaviors were analyzed using the Orowan and the dislocation density strengthening equation. And, a mechanism for the improved plasticity of EAT in AA7075-O was revealed.